ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN UNTUK MEMBOIKOT PRODUK ISRAEL (STUDI KASUS PADA KOMUNITAS JULID FISABILILLAH DI MEDIA SOSIAL TELEGRAM) - Alfi Lailatul Janah; Siti Badi’ah; Faisal Adnan Reza (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
The Israeli-Palestinian conflict has triggered a strong social response in Indonesia, one of which is through a movement to boycott products affiliated with Israel. The emergence of the Julid Fisabilillah community on Telegram social media is a concrete representation of the transformation of social movements from the physical to the digital realm. This study aims to analyze various factors influencing consumers' decisions to boycott Israeli products, with a focus on the Julid Fisabilillah community on Telegram social media. (Method) This study used a qualitative, analytical descriptive approach with a purposive sampling method. Data were obtained through interviews and documentation from key, primary, and additional informants who were actively involved in the community. The results show that internal factors such as religious values, empathy, and product knowledge, as well as external factors such as social media, framing (community calls), and the influence of public figures, significantly influence the decision to boycott. This study concludes that social media plays an active role in shaping digital collective consciousness, and grassroots movements such as Julid Fisabilillah are able to influence value-based consumption behavior. The implication is that online social movements can be an effective means of building social solidarity and encouraging social change based on ethical values and the dissemination of information